Alzheimer's disease clinical onset and age at death in people with Down syndrome: A systematic review and population‐based study. (31st December 2021) - Iulita, M. Florencia; Garzón, Diana; Bejanin, Alexandre; Tamayo, Natalia Valle; Videla, Laura; Altuna, Miren; Valldeneu, Sílvia; Barroeta, Isabel; Benejam, Bessy; Fernandez, Susana; Padilla, Concepción; Carmona‐Iragui, Maria; et al.
Abstract: Background: Despite better medical care and social support, life expectancy in people with Down syndrome (DS) is still close to 60 years, about 20 years less than in the general population. Alzheimer's disease (AD), which has a lifetime risk of >90% in DS, might be the cause. We conducted a systematic review to interrogate the age of onset of symptomatic AD and the age of death in this population. Methods: Our protocol was registered in the PROSPERO database (CRD42020203967). We performed a systematic search using PubMed, Embase, CINAHL and Web of Science. Only peer‐reviewed, original research studies written in English were considered. No time period restrictions were applied. Studies were eligible if they described research on adults with DS, had good methodological quality, and if they contained numerical results (mean and SD or standard error) of the following outcomes: age at onset or age at diagnosis of symptomatic AD (based on expert clinical judgment), age at death after onset of AD, and/or duration of the disease (time in years from onset or diagnosis to death). Results: We identified 6983 studies for title and abstract screening after duplicate removal. Of these, 259 articles were considered for full text review and 62 studies met the eligibility criteria (Figure 1). Excluded studies and reasons for exclusion are described in Figure 1. The weighted average for AD onset in DS was 54.1 ± 6.5 years (estimated in 4204 individuals) with a standard error of the mean across studies of 0.328. For age of death and disease duration the weighted averages were 57.7 ± 6.5 (data available from 514 individuals), and 5.4 ± 3.9 years (444 individuals), respectively. Conclusions: The mean age of AD onset in DS is remarkably consistent across studies, with a variability comparable to that reported in autosomal dominant AD. Given the >90% penetrance, the age of onset reported in the studies and the duration of the disease, life expectancy cannot possibly increase for people with DS if we do not find a cure for AD. This disease should therefore be recognized as the top medical and research priority in this population.